2019
DOI: 10.1021/acs.macromol.9b00492
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Attraction of Polymers toward Surfaces

Abstract: In polymer blends and block copolymers, one constituent (or segment type) is often enriched at the surface. This enrichment has important consequences for a variety of surface functions, including wettability, adhesive interactions, and fouling resistance, and can also influence the structure that forms deeper into the bulk. Herein, we review the thermodynamic principles that control the attraction of polymers toward surfaces, emphasizing cases where entropic effects associated with molecular weight or archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 159 publications
2
65
0
Order By: Relevance
“…[ 30 ] This behavior is enhanced in branched systems, including dendritic, where the number of chain‐ends is high. Additionally, entropically‐driven chain‐end surface segregation has been theoretically predicted [ 31–33 ] and experimentally shown [ 34–36 ] to induce surface wettability reversal, in which high energy components occupy the material surface. Thus, the strategic placement of antimicrobials on branched chain‐ends could result in a physically bound additive with surface active behavior.…”
Section: Figurementioning
confidence: 99%
“…[ 30 ] This behavior is enhanced in branched systems, including dendritic, where the number of chain‐ends is high. Additionally, entropically‐driven chain‐end surface segregation has been theoretically predicted [ 31–33 ] and experimentally shown [ 34–36 ] to induce surface wettability reversal, in which high energy components occupy the material surface. Thus, the strategic placement of antimicrobials on branched chain‐ends could result in a physically bound additive with surface active behavior.…”
Section: Figurementioning
confidence: 99%
“…Taking inspiration from these observations, films of PLA/CA and PLA/MDCA5 are hot melted at 180 °C between aluminum and Teflon sheets. The surface energy of aluminum is 39.5 mJ/m 2 , that of Teflon is 13.6 mJ/m 2 [ 44 ], and that of PLA is 42 mJ/m 2 [ 45 ]. CA has a polar group, and for this reason, it is expected that its migration is favored towards aluminum rather than towards Teflon that has a lower surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…The segregation of the chain end to the solid surface with no specific chemical interactions provides the minimization loss of conformational entropy at the interface [42,43]. Both SSP and PPP spectra of [N888H][DEHP] and [P8888] [DEHP] show three peaks at ~2850 cm −1 , 2870 cm −1 , and 2940 cm −1 , and the previous study has shown that the charged head groups of these IL molecules are preferentially interacting with the silica surface while their alkyl chains facing the bulk liquid (Figure 5b) [11,43]. The SSP spectrum of OFM has a very weak signal at ~2850 cm −1 (this peak was not captured well in the spectral fitting) while its relative intensity at ~2950 cm −1 (CH2,s,FR or CH2,as of C-CH2-O) is very strong.…”
Section: Sfg Spectra Of Individual Compounds At Silica/liquid Interfacementioning
confidence: 99%